Characterizing natural and recycled granular materials for (sub)base layers of roads by cyclic triaxial testing - Grégoire, Colette (2009)
The cyclic load triaxial test is a laboratory test which makes it possible to study the mechanical behaviour (resilient and permanent deformations) of unbound granular materials used in base and subbase layers of roads. This paper describes the equipment of the Belgian Road Research Centre and presents the first results obtained for a natural material commonly used in Belgium and two recycled materials (crushed concrete aggregate and steel slag). The influence of water content and the compaction method on resilient strains is analysed.